Knowledge of pediatricians regarding physical activity in childhood and adolescence - Alex Pinheiro Gordia; Teresa Maria Bianchini de Quadros; Luciana Rodrigues Silva; Gilton Marques dos Santos (Sociedade de Pediatria de São Paulo, 2015)
Objective: To investigate the knowledge and guidance given by pediatricians regarding physical activity in childhood and adolescence. Methods: A cross-sectional study involving a convenience sample of pediatricians (n=210) who participated in a national pediatrics congress in 2013. Sociodemographic and professional data and data regarding habitual physical activity and pediatricians' knowledge and instructions for young people regarding physical activity were collected using a questionnaire. Absolute and relative frequencies and means and standard deviations were calculated. Results: Most pediatricians were females, had graduated from medical school more than 15 years ago, and had residency in pediatrics. More than 70% of the participants reported to include physical activity guidance in their prescriptions. On the other hand, approximately two-thirds of the pediatricians incorrectly reported that children should not work out and less than 15% answered the question about physical activity barriers correctly. With respect to the two questions about physical activity to tackle obesity, incorrect answers were marked by more than 50% of the pediatricians. Most participants incorrectly reported that 30 min should be the minimum daily time of physical activity in young people. Less than 40% of the pediatricians correctly indicated the maximum time young people should spend in front of a screen. Conclusions: In general, the pediatricians reported that they recommend physical activity to their young patients, but specific knowledge of this topic was limited. Programs providing adequate information are needed.